2021
DOI: 10.2147/nss.s315556
|View full text |Cite
|
Sign up to set email alerts
|

To Nap or Not to Nap? A Systematic Review Evaluating Napping Behavior in Athletes and the Impact on Various Measures of Athletic Performance

Abstract: Purpose The objective of this systematic review was to 1) determine how studies evaluated napping behavior in athletes (frequency, duration, timing and measurement); 2) explore how napping impacted physical performance, cognitive performance, perceptual measures (eg, fatigue, muscle soreness, sleepiness and alertness), psychological state and night-time sleep in athletes. Methods Five bibliographic databases were searched from database inception to 11 August 2020. Obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 92 publications
(288 reference statements)
2
46
0
Order By: Relevance
“…Third, no inter-chronotype differences were investigated due to the small sample size of each sub-group. Fourth, athletes’ daytime napping behavior was not evaluated, and naps may represent a valid strategy for athletes to recover after nights of sleep restriction [ 37 ]. Fifth, pooling the sleep data of the four nights before the ATC (including the day of travel) introduced a potential confounding factor and, consequently, a real baseline sleep value was not obtained by the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Third, no inter-chronotype differences were investigated due to the small sample size of each sub-group. Fourth, athletes’ daytime napping behavior was not evaluated, and naps may represent a valid strategy for athletes to recover after nights of sleep restriction [ 37 ]. Fifth, pooling the sleep data of the four nights before the ATC (including the day of travel) introduced a potential confounding factor and, consequently, a real baseline sleep value was not obtained by the participants.…”
Section: Discussionmentioning
confidence: 99%
“…The eligibility criteria were specified according to the Population, Exposure, Outcomes, and Study (PEOS) framework for the research question [ 63 65 ]: "P" referred to high school and/or university students, comprising adolescents or adults of both sexes aged between 10–30 years; "E" corresponded to barriers to physical activity; "O" constituted the practice of physical activity; and "S" referred to studies with qualitative and quantitative designs published during any year in peer-reviewed journals in English, Spanish, or Portuguese.…”
Section: Methodsmentioning
confidence: 99%
“…However, the post hoc power analysis showed a statistical power of 63%. Fifth, diurnal naps are regarded as an advantageous intervention to enhance the recovery process and mitigate the negative effect of partial sleep deprivation on physical and cognitive performance ( Lastella et al, 2021 ; Souabni et al, 2021 ). In the present study, although nap records were found in several players’ sleep diaries, they were not habitual, so it was difficult for us to make further analyses on naps.…”
Section: Discussionmentioning
confidence: 99%